Epidemiological, diagnostic, clinical and morphological aspects of rabies in human - Golovchak, G; Sukhorukova, A; Markovsky, V; Sorokina, I; Borzenkova, I; Myroshnychenko, M; Pliten, O; Sakal, A (Annals of Mechnikov's Institute, 2020)
For humanity rabies is known over a millennium as one of the most dangerous zoonotic disease that is caused by the virus and is manifested by severe lesion of central nervous system with a high risk of death. In this article the authors presented the epidemiological, diagnostic, clinical and morphological aspects of rabies and the case of rabies in human from practice.